Association of hemodynamic variability during endovascular stroke treatment with functional outcome and parenchymal hemorrhage - Chen, Min; Sauer, Lukas; Potreck, Arne; Kieser, Meinhard; Bendszus, Martin; Ringleb, Peter A.; Möhlenbruch, Markus Alfred; Schönenberger, Silvia (Therapeutic advances in neurological disorders, 2025)
Background: Higher blood pressure variability (BPV) in patients suffering from acute ischemic stroke were shown to be associated with worse functional outcome and hemorrhagic transformation. - Objectives: To assess the influence of blood pressure variability during endovascular stroke treatment on functional outcome and parenchymal hemorrhage. - Design: We performed a post-hoc exploratory analysis of the individualized blood pressure management during endovascular thrombectomy under procedural sedation in acute ischemic stroke (INDIVIDUATE) study, which was a randomized clinical trial investigating an individualized blood pressure management strategy in comparison to a standardized treatment strategy during endovascular stroke treatment. - Methods: Several BPV parameters, such as procedure time of systolic blood pressure (SBP) in a range of a preprocedural baseline SBP ± 10 mmHg and ±20 mmHg, maximal and minimal SBP, variance and average real variability of intraprocedural SBP values were tested for association with functional outcome and PH1/PH2 hemorrhages in the current post-hoc analysis. - Results: Regression analyses were performed in 250 patients and revealed an association of variance of intraprocedural SBP (aOR, 1.002 (95% CI, 1.0004-1.004); p = 0.016) and average real variability of SBP (aOR, 1.105 (95% CI, 1.019-1.199); p = 0.016) with favorable outcome (modified Rankin Scale 0-2). - Conclusion: In our study, intraprocedural BPV parameters during endovascular stroke treatment were positively associated with favorable clinical outcomes. Potential underlying mechanisms should be further explored to better understand the effects of hemodynamics during the hyperacute time frame of endovascular stroke therapy. - Trial registration: Clinicaltrials.gov; NCT04578288.